RETRACTED ARTICLE - Parametric Design and Simulation of Control System for Automatic Voltage Stabilizer to Replace Manual Voltage Stabilizer in Low Voltage Power Grid - Trần Hùng Cường, (Journal of Technical Education Science, 2024)
The voltage stabilizer has the function of stabilizing the voltage within allowable limits. Therefore, designing and building a control system to help this device operate automatically will overcome the disadvantages of Voltage stabilizers are adjusted manually. This article presents the detailed parameter design and simulation of a combined PI and feed-forward control algorithm for automatic voltage stabilizers used in low-voltage power networks. This allows the device to completely automatically adjust the voltage without human intervention, this is due to the built-in controllers in the voltage regulator and automation for the voltage regulation process. The design process is applied to the input grid voltage range ranging from 150V to 290V and to the output voltage range supplied to electrical equipment always ranging from 210V to 230V, corresponding to a maximum deviation of 5 % of rated voltage value of low voltage grid (220V). This always ensures that electrical equipment operates well when the grid voltage fluctuates in a wide range. The implementation process is demonstrated by simulation on matlab/simulink software and an experimental system with a capacity of 10kVA.